Starting with Alice - Naylor, Phyllis Reynolds (Atheneum Books for Young Readers, 2012)
After she, her older brother, and their father move from Chicago to Maryland, Alice has trouble fitting into her new third grade class, but with the help of some new friends and her own unique outlook, she survives.